2022
DOI: 10.1039/d2dt01637k
|View full text |Cite
|
Sign up to set email alerts
|

Tetra germanium nonaselenide enwrapped with reduced graphene oxide and functionalized carbon nanotubes (Ge4Se9/RGO/FCNTs) hybrids for improved energy storage performances

Abstract: The development of multifunctional layered semiconductor materials and their carbonaceous hybrids as acceptable positive electrode materials for supercapacitor application is the key of interest. Ternary germanium selenide (Ge4Se9) with reduced...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The charge transfer resistance ( R ct ) is the resistance generated at the interface between the active material-coated electrode and electrolyte. 64 The R ct values of the MXene/P 2 W 18 and NW@MXene/P 2 W 18 electrodes were 70.84 and 66.68 Ω, respectively. NW@MXene/P 2 W 18 has a lower R ct value, indicating that the charge transfer between the electrolyte ions and the electroactive substances is easier.…”
Section: Resultsmentioning
confidence: 94%
“…The charge transfer resistance ( R ct ) is the resistance generated at the interface between the active material-coated electrode and electrolyte. 64 The R ct values of the MXene/P 2 W 18 and NW@MXene/P 2 W 18 electrodes were 70.84 and 66.68 Ω, respectively. NW@MXene/P 2 W 18 has a lower R ct value, indicating that the charge transfer between the electrolyte ions and the electroactive substances is easier.…”
Section: Resultsmentioning
confidence: 94%
“…5(b) illustrates the relationship between the current and scan rate at a particular potential. The current and scan rates were related to each other by the power law mentioned below: 47 i = av b where a and b are adjustable parameters.…”
Section: Resultsmentioning
confidence: 99%
“…The advancement of multifunctional materials and their carbonaceous hybrids as supercapacitor electrodes are of critical importance. Das et al [70] reported a supercapacitor based on the ternary germanium selenide (Ge 4 Se 9 ) with CNTs and reduced graphene oxide (RGO) and 1 M H 2 SO 4 as the electrolyte. They observed that the SC of the supercapacitor was 440 F/g with 98% coulombic efficiency after 5000 cycles.…”
Section: Introductionmentioning
confidence: 99%